Graphene and Graphene-Based Nanomaterials for DNA Detection: A Review - Xin Wu; Fengwen Mu; Yinghui Wang; Haiyan Zhao (Molecules, 2018)
DNA detection with high sensitivity and specificity has tremendous potential as molecular diagnostic agents. Graphene and graphene-based nanomaterials, such as graphene nanopore, graphene nanoribbon, graphene oxide, and reduced graphene oxide, graphene-nanoparticle composites, were demonstrated to have unique properties, which have attracted increasing interest towards the application of DNA detection with improved performance. This article comprehensively reviews the most recent trends in DNA detection based on graphene and graphene-related nanomaterials. Based on the current understanding, this review attempts to identify the future directions in which the field is likely to thrive, and stimulate more significant research in this subject.